The Response of Broiler Finisher Birds Fed Graded Levels of Yam Peel Meal in Place of Maize-Based Diets - Akinmutimi, A.H.; Onen, G.E. (International Journal of Poultry Science, 2008)
Performance of broiler finisher birds fed graded levels of yam peel meal in place of maize-based diets was investigated. 120 Anak broilers with likely equal weights were randomly allocated to 4 dietary treatments. Each treatment having 3 replicates with 10 birds per replicate in a completely randomized design (CRD). Diet 1 which was maize-based served as control, while yam peel meal quantitatively replaced 5%, 10% and 15% of maize meal in diets 2, 3 and 4 respectively. Each diet was offered ad libitum to the broiler birds for 28 days. Yam peel meal consists of 89.25 dry matter, 12.17 crude protein, 9.3 ash, 6.3 crude fibre, 1.05 crude fat and 2.980kcal/g gross energy. Anti-nutritional factors like tannin (0.57), saponin (0.87), oxalate (1.19), phytate (0.89), trypsin inhibitor (0.0) are in yam peel meal. There were no significant (P